UP'S: A Cohort Study on Recovery in Psychotic Disorder Patients: Design Protocol - van Aken, Bernice C.; Bakia, Ayuk; Wierdsma, André I.; Voskes, Yolande; Van Weeghel, Jaap; van Bussel, Evelyn M. M.; Hagestein, Carla; Ruissen, Andrea M.; Leendertse, Pien; Sewbalak, Wishal V.; van der Draai, Daphne A.; Hammink, Alice; et al. (Frontiers in Psychiatry, 2021)
Recovery is a multidimensional concept, including symptomatic, functional, social, as well as personal recovery. The present study aims at exploring psychosocial and biological determinants of personal recovery, and disentangling time-dependent relationships between personal recovery and the other domains of recovery in a sample of people with a psychotic disorder. A cohort study is conducted with a 10-year follow-up. Personal recovery is assessed using the Recovering Quality of Life Questionnaire (ReQoL) and the Individual Recovery Outcomes Counter (I.ROC). Other domains of recovery are assessed by the Positive and Negative Symptom Scale Remission (PANSS-R), the BRIEF-A and the Social Role Participation Questionnaire – Short version (SRPQ) to assess symptomatic, functional and societal recovery, respectively. In addition, multiple biological, psychological and social determinants are assessed. This study aims to assess the course of personal recovery, and to find determinants and time-dependent relationships with symptomatic, functional and societal recovery in people with a psychotic disorder. Strengths of the study are the large number of participants, long duration of follow-up, multiple assessments over time, extending beyond the treatment trajectory, and the use of a broad range of biological, psychological and social determinants.